Anisotropy effect on performance of PPM optical wireless oceanic communication links. (May 2019) - Baykal, Yahya
Highlights: BER of M-ary PPM OWOC link is studied in anisotropic weak oceanic turbulence. BER is found for various anisotropic turbulence parameters. Effects on BER of m in PPM, data bit rate, average gain of APD are examined. BER of M-ary PPM OWOC links is found to improve in anisotropic ocean. Abstract: The performance, quantified by the bit-error-rate ( BER ), of M-ary pulse position modulated (PPM) optical wireless oceanic communication (OWOC) link is investigated when such a link operates in anisotropic weak oceanic turbulence. For this purpose, formulations of the average received power and the scintillation index of collimated Gaussian optical beam detected by a point detector are developed for anisotropic weak oceanic turbulence, which in turn are employed in the BER expression of the PPM OWOC links. BER is evaluated under various turbulence parameters of anisotropic oceanic turbulence, M of M-ary PPM, data bit rate, average current gain of avalanche photodiode (APD). For any investigated parameter, it is found that the BER performance of M-ary PPM OWOC links is improved as the ocean becomes more anisotropic.